PENGARUH RASIO LIKUIDITAS (CURRENT RATIO, CASH RATIO DAN QUICK RATIO) TERHADAP KINERJA KEUANGAN PADA PT GARUDA INDONESIA (PERSERO), Tbk TAHUN 2013-2023 - Herlandi Putra, Irsan; Risha Rizyawati (JURNAL AKUNTANSI DAN SISTEM INFORMASI, 2025)
This study was conducted at PT Garuda Indonesia (Persero) Tbk with the aim of analyzing the impact of the current ratio, cash ratio, and quick ratio both simultaneously and partially on financial performance. The data used are the financial statements of PT Garuda Indonesia (Persero) Tbk from 2013 to 2023, taken from the official website of the Indonesia Stock Exchange (IDX). The sampling method used is purposive non-probability sampling, tailored to the research objectives and specific criteria, including the availability of financial statements for 11 consecutive years. The research approach used is quantitative, with descriptive and verificative methods. Data processing was conducted using statistical analysis, such as multiple linear regression, coefficient of determination, and hypothesis testing. The data analysis process was carried out using IBM SPSS Statistics version 27 software. The findings from the research indicate a significant correlation between the current ratio, cash ratio, and quick ratio. Based on the multiple linear regression analysis, all three ratios simultaneously affect financial performance. However, partially, the current ratio and cash ratio do not show a significant impact on financial performance.